Old wine in new bottles: A comparison of emerging market TNCs today and developed country TNCs thirty years ago - Dunning, JH; Kim, C; Park, D (SLPTMD (Department of International Development, University of Oxford), 2007)
Traditionally, the vast majority of transnational corporations (TNCs) that operate across borders have originated from developed countries such as the United States (US), Japan and members of the European Union (EU). Large and well-established TNCs such as Coca Cola, Toyota or Siemens are almost invariably from such countries. In the context of TNCs, we tend to associate the role of emerging markets2 primarily as the destination of TNCs from developed countries, for example, US software companies setting up research facilities in India, Japanese manufacturers establishing production facilities in China, or British banks acquiring financial institutions in Brazil. Until quite recently, this widespread perception of developed countries as homes of TNCs, and emerging markets as hosts of TNCs, had been firmly rooted in empirical reality (Dunning 1993). While, as will be described elsewhere in this chapter, there were TNCs from emerging markets in the past, they were nowhere near as active or visible as they are today.